PENGARUH PEMBIAYAAN JUAL BELI, PEMBIAYAAN BAGI HASIL, FINANCING DEPOSIT RATIO (FDR) DAN NON PERFORMING FINANCIAL (NPF) TERHADAP PROFITABILITAS BANK UMUM SYARIAH DI INDONESIA PERIODE 2010 - 2014 - Intan Khoirunnisa’ (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2015)
This study tries to determine the effect of Trade Financing, Profit Loss Sharing Financing, Financing to Deposit Ratio (FDR) and Non Performing Financing (NPF) on the profitability of Islamic Banks in Indonesia during 2010-2014, where profitability is measured by Return On Asset (ROA). The sample is selected through purposive sampling on six Islamic banks: Bank Muammalat, BRI Syariah, Bank Syariah Mandiri, Bank Syariah Bukopin, Bank Mega Syariah and Bank Panin Syariah. The primary data, the Quarterly Financial Report of the banks in 2010-2014, is obtained from from their websites. Multiple linear regression was employed to analyse the data. The finding shows that Trade Financing, Profit Loss Sharing Financing and FDR variable positively and significantly affects the ROA of Islamic Banks. The NPF variable negatively and significantly affects the ROA of Islamic Banks. Independent variable that dominantly affects ROA is Trade Financing. The predictive ability of the four variables on ROA is of 45,8%, while the rest are influenced by other factors beyond the research model. Keywords : Trade Financing, Profit Loss Sharing Financing, Financing to Deposit Ratio (FDR), Non Performing Financing (NPF) and Return On Asset (ROA)